The Effect of Stretching Exercises on the Quality of Life of Hemodialysis Patients with Restless Legs Syndrome - M Aliasgharpour; F Rafii; Z Abbasi (Iran University of Medical Sciences, 2014)
Abstract   Background & Aim: Restless leg syndrome is a common disorder among hemodialysis patients which decreases the quality of life of these patients. This study aims to determine the effect of stretching exercises on the quality of life of hemodialysis patients with restless leg syndrome.   Material & Methods: It was a randomized clinical trial. The sample consisted of 36 hemodialysis patients who were selected from the hemodialysis ward of one of the hospitals of Tehran using restless leg syndrome screening questionnaire. They were randomly assigned to either control (n=18) or experimental groups. Intra dialysis stretching exercises were applied three times a week for eight weeks and each time for half an hour on the patients 'legs. Data was collected by SF-36 before intervention and the end of the fourth and eighth weeks and was analyzed by Fisher, Mann-Whitney and Friedman tests using SPSS-PC (v.16).   Results: After eight weeks of intervention, the changes of the mean score of quality of life were significantly different in the intervention group compared with control group (P<0.001). Conclusion: According to the results, applying stretching exercises for eight weeks could increase the quality of life of hemodialysis patients by reducing the symptoms of restless leg syndrome. Accordingly, applying these exercises to improve the quality of life of hemodialysis patients with restless leg syndrome is recommended.